The content of some heavy metals in the wheat grain grown on Ovche Pole chernozems - Petkovski, Dime; Melovski, Ljupčo; Stojanovska-Petkovska, Rada (Macedonian Journal of Ecology and Environment, 1997)
The results of two year’s investigation of heavy metals (Mn, Fe, Zn, Cu, Co, Pb and Cd) in the wheat grain, cultivar "Radika", grown on Ovche Pole chernozems is presented in this article. In the experiment, fertilisers were used: macroelements (NPK) thorough the soil and microelements (Cu and Co) through the foliage in the phase of beginning of tillering. The soils were clayey loams or loamy clays, with low alkalinity, moderate humus and rich with total and available nitrogen after Turin and rich with available phosphorus and potassium after Al-method of Riehm. The content of heavy metals (microelements) in the grain were find to be in the allowable concentration, except for the Pb and Cd which were, after some fertilizer treatments, something above the maximum allowable concentration.